Cross-Cultural Adaptation and Validation of the Malay Version of Sports Motivation Scale-II - Ngien-Siong Chin (MDPI AG, 2021)
The 18-item Sport Motivation Scale (SMS-II) is one of the most-utilised scales measuring athletes’ motivation and its psychometric properties. However, we found no Malay version used to examine the Malaysian multi-ethnic population. Thus, the study aimed to translate and validate the SMS-II into the Malay version using confirmatory factor analysis. A total of 436 (16.44 ± 1.22) state athletes were asked to complete the SMS-II Malay version, which utilised the forward–backwards translation method. The results showed an acceptable fit with the data (CFI = 0.906, SRMR = 0.064; RMSEA = 0.056) and internal consistency, with a Cronbach’s alpha value that exceeded 0.50, which supported its usage for the assessment of motivation among the multi-ethnic Malaysian athletes. The Cronbach’s alpha values of all the factors were satisfactory, except for introjected regulation. Thus, further studies are needed to improve the reliability of such factors. Nonetheless, the Malay version of SMS-II was found to be valid and reliable for assessing the level of motivation of the multi-ethnic Malaysian athletes.